Examining the Effect of Auditor's Professional Skepticism on Fraud Risk Assessment, Considering Moderator Effect of Communication Skill and Social Undermining - Seyyed Hossein Hosseini (Shahid Bahonar University of Kerman, 2020)
Objective: The purpose of this study is to examine the effect of auditor's professional skepticism, PS, on the assessment of fraud risk, considering the moderator effect of communication skills and social undermining among 445 auditors working in public and private audit institutions in Tehran province. Method: This study is applied research in terms of the purpose, and a descriptive-survey type, using data from the year 2017. We examined the hypotheses in the forecasting model of relationships, and determined the moderator effect of communication skills and social undermining factors on the relationship between auditor's PS and fraud risk assessment, using the inferential statistics. The data was collected from a questionnaire and analyzed by a structural equation system using Amos software. Results: Findings showed that only two factors of six of the PS, including questioning mind and judgment suspension, have significant relationships with fraud risk assessment. Communication skill has positive and significant moderator effects on three indicators of the PS in fraud risk assessment, namely knowledge search, judgment suspension, and self-confidence. Also, findings indicated that social undermining has negative and significant moderator effects on the three indicators of the PS in fraud risk assessment. Conclusion: Because auditors' behavioral and ethical characteristics are effective in applying professional skepticism and fraud risk assessment, it is important to pay more attention to auditors' behavioral and ethical dimensions in the work environment.